Proceeding of Proceedings of the 9th International Symposium on Radiative Transfer, RAD-19 2019
DOI: 10.1615/rad-19.390
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Flash Method by Using a Conducto-Radiative Monte Carlo Algorithm : Application to Porous Media

Abstract: In the following paper, both conduction and radiation heat transfer were explored with a Monte-Carlo method applied to a complex geometry. The algorithm accounted for the coupling of conduction in the solid phase and radiation through the void phase and is used for direct simulation of a flash method. This allowed us to evaluate the effective total conductivity of the equivalent homogenized medium in function of a wide range of thermal, optical and geometric properties. The influence of the hemispherical emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This benchmark has been already used by Sans et. al [21] for the purpose of validating Monte Carlo simulations of coupled diffusion-radiation heat transfer. The open-porosity configuration corresponds to a heterogeneous 3D honeycomb that can be assimilated to a porous medium with open channels, like a heat exchanger configuration.…”
Section: Simulation Examplesmentioning
confidence: 99%
“…This benchmark has been already used by Sans et. al [21] for the purpose of validating Monte Carlo simulations of coupled diffusion-radiation heat transfer. The open-porosity configuration corresponds to a heterogeneous 3D honeycomb that can be assimilated to a porous medium with open channels, like a heat exchanger configuration.…”
Section: Simulation Examplesmentioning
confidence: 99%
“…2), the energy consumption may be computed by an expression similar to Eq. 2 that requires, T s,i (t) = 1 S i S i dA(⃗ y 0 ) T s (⃗ y 0 , t), (27) and the convective heat transfer coefficient (Tab. 2) which is set constant.…”
Section: Mean Radiant Temperature and Energy Consumptionmentioning
confidence: 99%
“…Although it is well-known that the Monte Carlo method (MCM) [11] can solve linear integrals whatever the domain size and number of dimensions, it has only recently been foreseen to solve for the temperature with a single MCM algorithm where conductionradiation-convection [12] are coupled. Early studies at steady-state [7,16] and transient [27] regimes have demonstrated the ability of MCM algorithms to solve for conductive, advective and radiative heat transfers in three-dimensional porous media with opaque solid surfaces and transparent fluid subdomains. Indeed, the heat transfer equation in a solid, with Robin's boundary condition (RBC), has been coupled to the radiative transfer equation (RTE) trough the double randomization technique (DRT) [21] allowing one to build conduction-advection-radiation random paths represented as broken lines linking the sources to a probe calculation point.…”
mentioning
confidence: 99%
“…For these reasons, MC has historically been used to model complex phenomenon and carry out high fidelity simulations, e.g., configuration factors for complex geometries [29][30][31][32][33][34][35][36][37][38], radiation heat transfer in porous, fibrous, and highly scattering turbid media [39][40][41][42][43][44][45], radiation between surfaces with strongly directionally dependent properties [46,47], combustion and flames [48][49][50][51][52][53][54][55], and shock waves [56]. The fact that MC usually provides an unbiased estimate with an unambiguous error estimate also makes it the default technique for validating and benchmarking other solution schemes [57][58][59].…”
Section: Traditional Applications Of Monte Carlo For Modeling Radiative Transfermentioning
confidence: 99%